THE STRATEGY OF CELEBRITY ENDORSER AND BRAND IMAGE IN DECISIONS ON SHAMPOO VARIAN HIJAB BUYING INTEREST - hijrah - wahyudi (Jurnal Ekonomi Integra, 2021)
This research aims to determine the strategy of celebrity endorser which is mediated by brand image in the decision to buy hijab shampoo. Data processing in this research uses the parametric-statistic specially analysis of Mediation using the software statistic JASP 0.14.1. Using primary data obtained from the result of filling questionnaire and secondary data obtained data source in the form of physical and digital literature. The results of this research derived from 100 respondents showed celebrity endorser which is mediated by brand image has a significant influence on the decision of hijabers to buy hijab shampoo. Popularity and manner of celebrity endorser can increase brand image of hijab shampoo. So, the company should be promote hijab shampoo by using the popular celebrity who have the good manner.